Bond graph modeling approach development for fuel cell PEMFC systems - Nedjem Eddine Benchouia; Elias Hadjadj Aoul; Lakhdar Khochemane; Bouziane Mahmah (www.elsevier.com/locate/he, 2014)
This paper addresses the problem of bond graph methodology as a graphical approach for modeling fuel cell systems. The system consists of a Proton Exchange Membrane Fuel Cell (PEMFC) stack, an interleaved boost converter, battery pack connected via a buck converter. Simulation results illustrate the simplified system response obtained using implementation of the governing equations in MATLAB/Simulink and is compared with a bond graph implementation in the simulation program 20-sim.